(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Chronic Kidney Disease (CKD) imposes a significant psychological burden on patients, which may evolve as the disease progresses from the pre-dialysis stage to requiring maintenance dialysis. Understanding this shift is crucial for delivering holistic care in resource-limited settings, such as Bangladesh. Objective: This study aimed to compare the levels of depression, anxiety, and stress between pre-dialysis and post-dialysis CKD patients. Methods: A comparative cohort study was conducted from July 2024 to June 2025 at Eastern Medical College & Hospital (EMCH) and another tertiary care hospital. A total of 80 participants were recruited, comprising 40 in the pre-dialysis (CKD stage 4 and 5) group and 40 in the post-dialysis (on maintenance hemodialysis for more than 3 months) group. The Depression, Anxiety, and Stress Scale (DASS-21) were used for psychological assessment. Data were analyzed using SPSS version 23.0, employing independent t-tests and Chi-square tests. Results: The post-dialysis group demonstrated significantly higher mean scores for depression (18.4 vs. 11.2, p<0.001), anxiety (15.7 vs. 9.8, p<0.001), and stress (19.6 vs. 13.1, p<0.001). A significantly greater proportion of dialysis patients also met the threshold for severe depression (35% vs. 12.5%, p=0.012) and anxiety (30% vs. 10%, p=0.025). A significant negative correlation was found between eGFR and all psychological distress scores (p<0.01). Conclusion: Initiation of dialysis is associated with a severe increase in psychological morbidity among CKD patients in Bangladesh. Integrating routine mental health screening and support into standard nephrology care is strongly recommended to address this significant burden. J Com Med Col Teachers’ Asso Jan 2026; 30(1): 35-39